2015
DOI: 10.1016/j.nanoen.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Tandem structured spectrally selective coating layer of copper oxide nanowires combined with cobalt oxide nanoparticles

Abstract: Tandem structured spectrally selective coating layer of copper oxide nanowires combined with cobalt oxide nanoparticles, Nano Energy, http://dx.Abstract Increasing the light absorption across the wide solar spectrum has important implications for applications in solar-thermal and photovoltaic energy conversion. Here, we report novel tandem structures combing two different materials with complementary optical properties and microstructures: copper oxide (CuO) nanowires (NWs) and cobalt oxide (Co 3 O 4 ) nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A possible drawback of broadband absorbing devices is related to infrared thermal radiation loss, an effect that becomes important at higher sun concentrations and high temperatures. To address this issue, a selective absorber with judiciously positioned cutoff wavelengths can help suppressing infrared absorption and minimizing radiation loss . More recently, another Au nanoporous structure exhibiting a cutoff wavelength was proposed in ref.…”
Section: Harnessing Optical Chaos For Renewable and Clean Energy Techmentioning
confidence: 99%
“…A possible drawback of broadband absorbing devices is related to infrared thermal radiation loss, an effect that becomes important at higher sun concentrations and high temperatures. To address this issue, a selective absorber with judiciously positioned cutoff wavelengths can help suppressing infrared absorption and minimizing radiation loss . More recently, another Au nanoporous structure exhibiting a cutoff wavelength was proposed in ref.…”
Section: Harnessing Optical Chaos For Renewable and Clean Energy Techmentioning
confidence: 99%
“…[5] Most of the coating technologies involve vacuum (physical and chemical) deposition [5] and sputtering, [7][8][9] whereas only af ew comprise wet depositionp rocesses. [3,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Amongt he application techniques used for wet coating are spin coating, [11][12][13] roll-and coil-coating, [14][15][16] dip coating, [17][18][19] and spraying. [14,18,[20][21][22][23] Recently,A mri et al reviewed the progress in the production of flat plate solar selective absorber materials by sol-gel methods and demonstrated that the optical properties and stability of the selective coating can be simply controlled by tuning the reactionc onditions during the synthesis course.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Very recently,K im et al fabricated tandem structures of spectrally selectivec oatings using copper oxide nanowires and cobalt oxide nanoparticles by employing three differentm ethods: spray coating, dip coating, and transferring. [22] Theb est absorbing material ever produced consists of carbon nanotubes (CNTs). CNTs only reflect light weakly but they also absorb light strongly.B ecause of their unique optical properties,C NTs are excellent candidates for solar absorber coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Although this provides an elegant proof-of-concept, tungsten is easily oxidized and so is not suitable for ambient CSP receivers. More complex nanostructures are under consideration as selective absorber coatings, but it remains to be seen if these materials can be produced cost effectively 10 .…”
mentioning
confidence: 99%